2019
DOI: 10.21037/atm.2019.10.105
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal subpopulations of peripheral blood lymphocytes are involved in Parkinson’s disease

Abstract: Background: Abnormal immune responses are involved in the development of Parkinson's disease (PD), and also affect peripheral blood lymphocytes. The profile of lymphocyte subsets in peripheral blood and whether it is relevant to the clinical features of PD patients remains controversial.Methods: To explore the role of peripheral blood lymphocytes (NK cells, B cells, CD3 + T cells, CD3 + CD4 + T cells and CD3 + CD8 + T cells) in the development of PD, a case-control study including 127 patients and 148 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 59 publications
(58 reference statements)
4
31
0
3
Order By: Relevance
“…This complex disease is likely of autoimmune origin, but many questions remain unanswered despite a vast amount of available literature. On the one hand, several studies have reported the alteration of the percentage of peripheral blood T cells in PD patients 10 , but the relative contribution of each cell subtype to the disease etiology remains unclear 10 . On the other hand, CD8 + and CD4 + T cells were reported to invade the brain in both postmortem human PD specimens and in the mouse model of PD 9,11 , but the composition and interaction of T cell subtypes in human peripheral blood and cerebrospinal fluid and their potential ability to infiltrate the central nervous system remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This complex disease is likely of autoimmune origin, but many questions remain unanswered despite a vast amount of available literature. On the one hand, several studies have reported the alteration of the percentage of peripheral blood T cells in PD patients 10 , but the relative contribution of each cell subtype to the disease etiology remains unclear 10 . On the other hand, CD8 + and CD4 + T cells were reported to invade the brain in both postmortem human PD specimens and in the mouse model of PD 9,11 , but the composition and interaction of T cell subtypes in human peripheral blood and cerebrospinal fluid and their potential ability to infiltrate the central nervous system remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the involvement of peripheral adaptive immunity in PD (Kustrimovic et al, 2018;De Francesco et al, 2021), and the decrease of overall numbers of lymphocytes in PD patients (Bas et al, 2001;Calopa et al, 2010). Moreover, the peripheral immune change in PD patients was evidenced by decreased percentage of CD3+ T lymphocytes and CD4+ T lymphocytes in peripheral blood (Cen et al, 2017;Rocha et al, 2018;Sun et al, 2019). The reduced circulating CD4+ T lymphocytes in PD patients were shown to be caused by the reduction in Th2, Th17, and Treg (Kustrimovic et al, 2018), and the reduction of CD4+ T cells was worsened with increasing clinical severity (Stevens et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Болезнь Паркинсона (БП) -нейродегенеративное заболевание, основными признаками которого являются прогрессирующая гибель дофаминергических (DA) нейронов, появление телец Леви, содержащих агрегаты α-синуклеина, и хроническое нейровоспаление [1, 2, 3, 4, 5]. Наряду с активацией микроглии и повышенной лимфоцитарной инфильтрацией в центральной нервной системе (ЦНС), воспаление при БП сопровождается изменением состава и фенотипа периферических иммунных клеток [4,5,6,7]. Существующие данные указывают, главным образом, на ключевую роль в патогенезе БП периферических Тклеток и их субпопуляций [4,5,6,7].…”
Section: Introductionunclassified
“…Наряду с активацией микроглии и повышенной лимфоцитарной инфильтрацией в центральной нервной системе (ЦНС), воспаление при БП сопровождается изменением состава и фенотипа периферических иммунных клеток [4,5,6,7]. Существующие данные указывают, главным образом, на ключевую роль в патогенезе БП периферических Тклеток и их субпопуляций [4,5,6,7]. Вместе с тем всё большее внимание в последнее время привлекают В-клетки, которые являются важными компонентами адаптивной иммунной системы и включены в патогенез многих заболеваний ЦНС [8].…”
Section: Introductionunclassified
See 1 more Smart Citation